Identification of river valley areas threatening the chemical status of groundwater, in the example of the upper course of the Ner River basin, central Poland - Krogulec, Ewa; Małecki, Jerzy J.; Szostakiewicz-Hołownia, Marzena; Trzeciak, Joanna; Zabłocki, Sebastian; Ziułkiewicz, Maciej (Quaestiones Geographicae, 2024)
The planning and management of water in the river basins require the identification of places where the quality of groundwater is being threatened. The risk of launching the accumulated pollutants present in the solid phase of the soil may be caused by both the changes in the pressure gradients in the aquifers and the changes in the hydrogeochemical balances. In the example of the Ner river valley, into which wastewater from the Łódź agglomeration has been discharged, the factors threatening the chemical status of groundwater were determined. This assessment was carried out based on the results of the determination of the hydrodynamic balance disturbances in the Upper Cretaceous formations, model studies of groundwater flow and hydrogeochemical studies conducted on the sorption complex of the Ner alluvium as well as the chemistry of the river water, alluvial water and groundwater. The results showed that the river water is heavily anthropogenically transformed. Model studies have shown that when the Ignacew -intake wells are pumped collectively, the inflow takes place through the Ner valley, where the hydrogeological window between the Quaternary and the Upper Cretaceous aquifers is found. The withdrawal by the Ignacew intakes may result in the reversal of piezometric pressures in the valley, which creates the possibility of the infiltration of polluted surface water into groundwater. Observations indicate the need to take into account the zones where surface water and water from the river alluvium are a real threat to the chemical status of the aquifers. These aspects are important when determining the protection zones and in renewable and disposal resource assessments of the Main Groundwater Reservoirs.